2007
DOI: 10.1111/j.1540-8175.2007.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Remodeling in Acute Anterior Myocardial Infarction

Abstract: An increase in the diameter, volume, and dimensions of LA during atrial remodeling was detected. LA passive emptying fraction was found to decrease, whereas atrial active emptying function was found to increase to compensate for this change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(65 reference statements)
3
9
0
Order By: Relevance
“…Our findings are also in line with study by Bozkurt et al [4] where echocardiography was performed on admission and after a week, 1 and 3 months, showing that LA volume increased significantly starting from hospital admission. The compensatory mechanism of stroke volume increase responded to volume change, but the difference became significant after a period of 1 month [4]. Left atrial remodeling, defined as increase in LA volume of 8 ml/m 2 has been shown to occur in about one fifth of patients after AMI leading to LA functional deterioration over a 12-month period [5].…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Our findings are also in line with study by Bozkurt et al [4] where echocardiography was performed on admission and after a week, 1 and 3 months, showing that LA volume increased significantly starting from hospital admission. The compensatory mechanism of stroke volume increase responded to volume change, but the difference became significant after a period of 1 month [4]. Left atrial remodeling, defined as increase in LA volume of 8 ml/m 2 has been shown to occur in about one fifth of patients after AMI leading to LA functional deterioration over a 12-month period [5].…”
Section: Discussionsupporting
confidence: 95%
“…This mechanism is functional up to certain LA volumes when increased volume load cannot be further compensated by increased work and LA further dilates, indicating that Frank-Starling mechanism is also operative in the LA [28]. Our findings are also in line with study by Bozkurt et al [4] where echocardiography was performed on admission and after a week, 1 and 3 months, showing that LA volume increased significantly starting from hospital admission. The compensatory mechanism of stroke volume increase responded to volume change, but the difference became significant after a period of 1 month [4].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The means of the LAEF in this study were consistent with the LAEF values of this study. Bozkurt et al [31] studied LA remodeling in 65 AMI patients who were treated with conventional therapy, and they did not find a significant change in the LAEF during the 3-month follow-up. Similarly, our study did not show any change in the LAEF of conventional therapy group.…”
Section: Atrial Volumes and Sizesmentioning
confidence: 96%
“…Left atrium (LA) enlargement, as determined by echocardiography, is an important predictor of cardiovascular outcome [1][2][3][4]. LA enlargement is associated with a poor exercise tolerance [5], and is predictive of future stroke, atrial fibrillation, and death [4,6].…”
Section: Introductionmentioning
confidence: 99%